The Influence of Service Quality Dimensions on Public Satisfaction at the Balusu Sub-district Office, Barru Regency - Warni; Syahrir; Musralin (LP2M IAIN Palopo, 2025)
The purpose of this study is to determine the Influence of Service Quality Dimensions on Public Satisfaction at the Balusu District Office, Barru Regency. The analytical methods used in this study are simple linear regression analysis, T test, correlation analysis and determination. The results of the study indicate that the hypothesis of service quality dimensions on public satisfaction is accepted on the basis of the calculated T value of 5.549 which is greater than the T table value of 1.7108 then the results of the correlation coefficient test show that the service quality dimensions on public satisfaction have a strong relationship, then based on the results of the determination test shows that the contribution of service quality dimensions is 54.4% to the public satisfaction variable.